Statistical study of the control of Jupiters decametric radio emissions by the satellite Europa - Hadassa Raquel Peixoto Jácome (2020)
Jupiter is an intense source of Auroral Radio Emissions (AREs). Such emissions originate from resonance between non-relativistic electrons gyrating along Jupiters magnetic field lines and electromagnetic waves, in the Cyclotron maser instability. The jovian AREs in the Decametric (DAM) wavelength range can be detected from ground-based instruments on the Earth for having frequencies that surpass the cutoff frequency of the Earths ionosphere. The occurrence of the jovian AREs is partially controlled by the Galilean satellites Io, Europa and Ganymede. The satellite control occurs by emissions induction through field-aligned electric currents resulting from the interaction between the satellites and the magnetospheric plasma along their orbit. Evidence of this control is the nonuniform occurrence of jovian DAM emissions along the satellites orbital phase and the observers longitude. Such evidence was firstly observed in 1955 for Io and has been found also for Ganymede and for Europa. The continuous observation of Jupiters radio emissions by the Nançay Decameter Array (NDA) along the years has enabled the gathering of an extensive digital data catalog with 29 years of daily observations. This catalog has already provided statistical evidences of the control of the jovian DAM emissions by Io and Ganymede, as well as the possibility of further selection and analysis of emissions. This work main objective was to analyze this NDAs catalog to select and analyze jovian DAM emissions possibly induced by the satellite Europa. As results, we were able to detect and characterize possible Europa-induced (Eu-DAM) emissions from two different sources, A and C, on Jupiter. Statistical distribution parameters, such as the median, mean and standard deviation, for these emissions maximum frequency, duration and intensity have been found for the first time. Main maximum frequency ranges of the analyzed Eu-DAM emissions were suggested. Moreover, the Eu-A and Eu-C emissions selected in this work were also compared with the Eu-A and the Eu-C emissions observed in previous works on the databases of the Voyagers 1 and 2 and Cassini, and with Io- and Ganymede-induced emissions on the NDAs catalog.